Origines et étapes de la diversité des techniques sidérurgiques en Afrique de l’Ouest : le cas de la production du fer en pays bassar (nord du Togo) du XIIIe au XXe siècles - Caroline Robion-Brunner; Marie-Pierre Coustures; Stéphan Dugast; Assouman Tchetre-Gbandi; Didier Béziat (Afriques)
Iron production has played a key role in the history of Africa for more than 3,000 years. The study of this human activity has demonstrated its exceptional significance, its historical antiquity and an astonishing variability of practice. Indeed, metallurgists developed different ways to smelt iron ores in Sub-Saharan Africa. They multiplied the technical choices to a degree unequalled on other continents.The region of Bassar (northern Togo) is known to be one of the oldest ‒ ironmaking began there in the 5th century BCE ‒ and most important iron production centers in West Africa ‒ approximately 50,000 tons of iron were produced there between the 13th and 20th centuries. Recent research conducted within the international and interdisciplinary program SidérEnT (2014-2018) revealed the existence of several iron smelting technics there. In order to understand which factors could be at the origin of this, we have taken the most holistic approach possible. Thus, after establishing an exhaustive assessment of the geological, archaeological, archaeometric and ethnological data at our disposal, we evaluate the different possibilities that can explain the plurality of practices and then we propose different historical-cultural scenarios tracing the evolution of iron smelting technics in the Bassar region.